Perencanaan Pembangunan Infrastruktur Jalan Di Desa Soni Kecamatan Dampal Selatan Kabupaten Toli-Toli - Andini; Hattab, Syahruddin; Mayusa, Askar (JPS: Journal of Publicness Studies, 2025)
Road infrastructure development is a crucial aspect in supporting the improvement of community welfare and mobility in rural areas. This study aims to describe and analyze the planning of road infrastructure development in Soni Village, Dampal Selatan Subdistrict, Toli-Toli Regency. The research employed a descriptive qualitative approach using data collection techniques such as observation, interviews, and documentation. Informants in this study included the village head, head of the Village Consultative Body, educational figures, religious leaders, women's representatives, and local residents. The results show that the planning process has gone through the formulation stage in a participatory manner through hamlet-level deliberations; however, the plan determination stage still faces challenges due to limited community involvement in official planning forums. Implementation control was carried out by the village implementation and supervision teams, although land acquisition issues remain unresolved. Meanwhile, the evaluation stage has not been conducted in a structured manner and lacks instruments to measure the impact or community satisfaction. The conclusion of this study indicates that the planning stages have generally followed participatory development principles, but improvements are needed in implementation and evaluation aspects to ensure that road development in Soni Village proceeds more effectively and sustainably.